1997
DOI: 10.1071/ea96133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of harvest maturity on the storage life of Japanese type plums

Abstract: Summary. Plums are highly perishable and once harvested have a short commercial life. Hence, this crop would benefit from the determination of conditions which permit extended storage. This study investigates the effects of fruit maturity at harvest on the physical and chemical characteristics of the plum cultivars, Radiant, Gulfruby and Shiro, after periods of cool storage. Fruit from these cultivars were separated into 3 maturity categories according to either skin colour at harvest or time after pit hardeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 0 publications
6
18
0
1
Order By: Relevance
“…The higher oleic/linoleic acid ratio, higher total and reduced ascorbic acid concentrations and total phenolic concentration in all probability render 'Angeleno' plums much more CI resistant under long term cold-storage conditions compared to 'Sapphire' plums. The results of this study confirm the observation of Abdi et al (1997) that fruit with a long fruit development period are less susceptible to CI compared to fruit with a short fruit development period. In our study it was found that the longer fruit development period causes 'Angeleno' to experience higher average day temperatures than 'Sapphire' which, in turn, causes higher levels of MUFA instead of PUFA to accumulate in the 'Angeleno' fruit.…”
Section: Resultssupporting
confidence: 92%
“…The higher oleic/linoleic acid ratio, higher total and reduced ascorbic acid concentrations and total phenolic concentration in all probability render 'Angeleno' plums much more CI resistant under long term cold-storage conditions compared to 'Sapphire' plums. The results of this study confirm the observation of Abdi et al (1997) that fruit with a long fruit development period are less susceptible to CI compared to fruit with a short fruit development period. In our study it was found that the longer fruit development period causes 'Angeleno' to experience higher average day temperatures than 'Sapphire' which, in turn, causes higher levels of MUFA instead of PUFA to accumulate in the 'Angeleno' fruit.…”
Section: Resultssupporting
confidence: 92%
“…Kader et al (1999) observed a linear decrease of chlorophyll during the last development period of plum fruit, for both varieties researched, which is agreement with horticultural knowledge of fruits ripening. In another study, Abdi et al (1997) reported a similar chlorophyll degradation pattern, the studied plum varieties changed the color from green to yellow.…”
Section: Estimation Of Total Flavonoid Contentmentioning
confidence: 80%
“…Kader et al (1999) have observed a linear decrease in chlorophyll absorption in the last development of plum fruit on the tree for both varieties studied, which corresponds physiologically and horticulturally with the growth and maturation of the fruit. Abdi et al (1997) stated that green-to-yellow color change for prunes in its research is associated with chlorophyll degradation during fruit baking. A decrease of the chlorophyll content by 41% during 12 days of ripening, was also reported for the peel of 'Qingnai' plums (Prunus salicina Lindl.…”
Section: Chlorophyll Contentmentioning
confidence: 99%
“…Segundo Crisosto et al (2004), ameixas 'Blackamber', quando colhidas precocemente, são mais suscetíveis a dano por frio manifestado, como polpa escurecida, e, quando colhidas tardiamente, são mais suscetíveis a dano por frio manifestado, como polpa translúcida. Outros estudos, com várias cultivares de ameixas, mostram que, em frutos colhidos em estádio avançado de maturação, o dano por frio manifesta-se na forma de polpa gelatinosa (ABDI et al, 1997).…”
Section: Introductionunclassified